2010
DOI: 10.1111/j.1540-6261.2009.01543.x
|View full text |Cite
|
Sign up to set email alerts
|

Financial Structure, Acquisition Opportunities, and Firm Locations

Abstract: This paper investigates the relation between firms' locations and their corporate finance decisions. We develop a model where being located within an industry cluster increases opportunities to make acquisitions, and to facilitate those acquisitions, firms within clusters maintain more financial slack. Consistent with our model we find that firms located within industry clusters make more acquisitions, and have lower debt ratios and larger cash balances than their industry peers located outside clusters. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
79
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(90 citation statements)
references
References 52 publications
9
79
0
Order By: Relevance
“…Using data from a sample of 25 companies during 1999 to 2009 on the Greek stock exchange, Afza and Mirza (2010) indicate that the dividend policies and its treatment is the most important for the investors (Afza and Mirza, 2010). In another study, Almazan et al (2010) also examined the effect of the financial leverage on the dividend policies in the companies of Karachi. The result of their study indicated a negative and significant relationship between financial leverage and amount of divisible profit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using data from a sample of 25 companies during 1999 to 2009 on the Greek stock exchange, Afza and Mirza (2010) indicate that the dividend policies and its treatment is the most important for the investors (Afza and Mirza, 2010). In another study, Almazan et al (2010) also examined the effect of the financial leverage on the dividend policies in the companies of Karachi. The result of their study indicated a negative and significant relationship between financial leverage and amount of divisible profit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Almazan et al (2010) develop an analytical model in support of the view that geographically clustered firms tend to have more investment opportunities, and require increased cash holdings to undertake more acquisitions. Landier et al (2009) show that firms' geographic dispersion substantially affects labor and divestiture policies.…”
Section: Introductionmentioning
confidence: 99%
“…2 In our model the merger setting exhibits features similar to the internal capital markets in that the post-merger firm has two employees, allowing the firm to create value as long as at least one of them is successful. This feature is similar to winner picking advantage of internal capital markets identified in Stein (1997).…”
Section: Introductionmentioning
confidence: 99%